2013
DOI: 10.3390/cancers5031177
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes in Newly Diagnosed Elderly Glioblastoma Patients after Concomitant Temozolomide Administration and Hypofractionated Radiotherapy

Abstract: This study aimed to analyze the treatment and outcomes of older glioblastoma patients. Forty-four patients older than 70 years of age were referred to the Paul Strauss Center for chemotherapy and radiotherapy. The median age was 75.5 years old (range: 70–84), and the patients included 18 females and 26 males. The median Karnofsky index (KI) was 70%. The Charlson indices varied from 4 to 6. All of the patients underwent surgery. O6-methylguanine–DNA methyltransferase (MGMT) methylation status was determined in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2014
2014
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 41 publications
0
11
0
1
Order By: Relevance
“…CLIO-ICT synergized with temozolomide in vivo , thereby revealing a novel therapeutic combinatorial regimen for targeting GBMs. Current GBM therapies include surgical resection followed by radiation therapy with concurrent temozolomide (TMZ) treatment (41). However 90% of GBM patients develop tumor recurrence (42).…”
Section: Discussionmentioning
confidence: 99%
“…CLIO-ICT synergized with temozolomide in vivo , thereby revealing a novel therapeutic combinatorial regimen for targeting GBMs. Current GBM therapies include surgical resection followed by radiation therapy with concurrent temozolomide (TMZ) treatment (41). However 90% of GBM patients develop tumor recurrence (42).…”
Section: Discussionmentioning
confidence: 99%
“…However, the optimal treatment strategy for older patients remains controversial. Although the addition of RT, compared to best supportive care, may be associated with better survival outcomes and equivalent quality of life outcomes in the elderly, the optimal RT dose fractionation and the benefit of chemotherapy in this population is an area of active investigation .…”
Section: Introductionmentioning
confidence: 99%
“…Only a few studies have reported on the use of hypofractionated RT in combination with TMZ [21,39,40]. We recently conducted a phase 2 trial on the efficacy of an abbreviated RT course (40 Gy in 15 fractions over 3 weeks) plus concomitant and adjuvant TMZ chemotherapy for up to 12 cycles in 70 patients aged C70 years with newly diagnosed GBM [39].…”
Section: Combined Chemoradiationmentioning
confidence: 99%